Carta de Luis Muñoz Marín a Roberto H. Todd - Muñoz Marín, Luis; Todd, Roberto H. (My University, 1937)
Carta relacionada a las manifestaciones públicas de Antonio R. Barceló.
Keywords: Barceló, Antonio R., 1868-1938; Partido Liberal Puertorriqueño